Antidopaminergic antiemetics and trauma‐related hospitalization: A population‐based self‐controlled case series study. Issue 3 (12th August 2020) - Bezin, Julien; Noize, Pernelle; Mansiaux, Yohann; Jarne, Ana; Pariente, Antoine
Abstract : Aims: The aim of this study was to evaluate the risk of trauma associated with the use of antidopaminergic antiemetics in a real‐world setting. Methods: A self‐controlled case series analysis was performed using the EGB database, the representative sample of the French national healthcare insurance system database. All subjects aged 18 years and over who presented with at least 1 trauma‐related hospitalization and 1 supply for domperidone, metoclopramide or metopimazine between 2009 and 2014 were included in the study. Associations were evaluated by incidence rate ratios. Results: Included exposed cases were 7610 for domperidone cohort, 2189 for metoclopramide and 3911 for metopimazine. Incidence rate ratio for trauma‐related hospitalization during the first 7 days of exposure period compared to unexposed period was 1.53 (95% confidence interval 1.29–1.80) for domperidone, 2.00 (1.37–2.91) for metoclopramide and 2.30 (1.71–3.09) for metopimazine. Conclusion: We found an increased risk of hospitalizations for traumatic injuries for the main marketed antidopaminergic antiemetics during the first days of use. The highest risk was observed for metopimazine, which could relate to its pharmacological profile and central effects.